S7A:7 Administration of serpinb3 delays glomerulonephritis and attenuates the lupus-like disease in lupus murine models by an immunomodulatory effect. (21st March 2018) - Gatto, M; Cavicchioli, L; Luisetto, R; Codolo, G; Maggioni, G; Saccon, F; Beggio, M; Pontisso, P; Ghirardello, A; Doria, A
Abstract : Background: Abnormal apoptosis and clearance of cellular debris concur to development of systemic lupus erythematosus (SLE). SERPINS (serin-protease inhibitors) are ancient molecules regulating immune homeostasis. SERPINB3 modulates apoptosis and is hypoexpressed on SLE B cells. Aim: To explore the effects of SERPINB3 administration in murine lupus models, focusing on glomerulonephritis. Methods: NZB/W F1 and MRL/lpr mice were used. 40 NZB/W F1 mice were divided into 4 groups of 10 mice each and intraperitoneally injected twice a week starting before occurrence of proteinuria traces (group 1 and 2, prophylactic approach) or after development of proteinuria 30 mg/dl (group 3 and 4, therapeutic approach) with hrSERPINB3 (7.5 µg/0.1 mL prophylactic approach, or 15 µg/0.1 mL therapeutic approach) or PBS (0.1 mL). 20 MRL/lpr mice were injected with hrSERPINB3 (group 5, n=10) or PBS (group 6, n=10) with a prophylactic approach. We assessed time of occurrence and titers of anti-dsDNA and anti-C1q antibodies by ELISA; proteinuria and serum creatinine; overall- and proteinuria-free survival. Six NZB/W F1 mice were sacrificed at week 27, while 10 MRL/lpr mice at week 13 and another 10 at 16/18 weeks for histological kidneys comparison. Flow-cytometry was performed on MRL/lpr splenocytes. Non parametric tests were performed for statistics; proteinuria-free (<300 mg/dl) and overall survival were evaluated by Kaplan-Meier method. Results: Levels of autoantibodies were significantly decreased and delayed in group 1 vs group 2, group 3 vs group 4, and group 5 vs group 6 (p<0.0001 for all). Proteinuria levels were significantly reduced and proteinuria-free and overall survival were significantly improved in SERPINB3 groups vs controls (figure 1). No differences were found among creatinine serum levels. Histological analysis showed a lower prevalence of severe tubular lesions in group 5 vs group 6 MRL/lpr mice at week 16 (chi-squared p=0.014), and mice belonging to SERPINB3 groups showed a trend toward a reduced prevalence of severe glomerular and tubular lesions. Th17:Treg ratio significantly decreased due to a remarkable increase in Treg levels in MRL/lpr mice treated with SERPINB3. Conclusions: Administration of SERPINB3 significantly improves disease and delays the onset of severe glomerulonephritis in lupus-prone mice. SERPINB3 may influence immune-cell function through immunoregulatory effects involving promotion of Treg.